Writing silver travel: Examining the peripheral in senior travel blogs - Azariah, Deepti (2018)
There is a growing recognition that senior tourism has significant socioeconomic benefits for countries with ageing populations (Bates, 2004; Small, 2003; Vojvodic, 2015) and that the practices of older travellers need further investigation. Seniors are often relegated to the wrong side of the digital divide and, although this gap is rapidly diminishing (McMurtrey, Zeltmann, Downey, & McGaughey, 2011), the critical examination of senior travel bloggers, or silver tourists, and their narratives remains on the peripheries of academic debate. In response to a need for further research into “digital seniors” (Quan-Haase, Martin, & Schreurs, 2016) and their online narratives, this paper explores the concept of the peripheral within the context of senior travel blogs and asks how these narratives both embrace and challenge the notion of core/periphery. To answer this, the paper draws on various theories of travel and social media and aims to offer a nuanced understanding of how these narratives negotiate the persistent tensions between Home and Away, Self and Other, and escape and social connectedness, which concepts and discourses are integral to the writing and practice of silver travel.